Advanced Culture Techniques of Thalassiosira sp. as Natural Feed for Vannamei Pacific Whiteleg Shrimp Larvae (Litopenaeus Vannamei): A Case Study at Center For Superior Shrimp and Shellfish Broodstock Production (BPIU2K) - Fitri, Miftahul; Muahiddah, Nuri (Journal of Vocational in Aquaculture (JAVA), 2025)
The stepwise culture technique of Thalassiosira sp., is a method used to produce natural feed for Pacific whiteleg shrimp larvae (Litopenaeus vannamei) at BPIU2K Karangasem, Bali. Thalassiosira sp., a microalgae species is known for its high nutritional content, making it an ideal natural feed for aquaculture. The objectives are to analyze the influence of various culture conditions on the growth and nutritional quality of Thalassiosira sp., assess its impact on the growth performance and survival rates of shrimp larvae, and identify potential challenges and solutions in the culture process. The research also identifies challenges in culturing processes, such as maintaining optimal environmental conditions and ensuring consistent nutrient levels. The results demonstrate the effectiveness of the stepwise culture technique in achieving high-density growth of Thalassiosira sp., which positively impacts the growth and survival rate of vannamei shrimp larvae. The culture method involves a stepwise process conducted at the BPIU2K Karangasem, progressing from laboratory scale to intermediate (semi-mass) and mass culture. Results show that plankton growth in Erlenmeyer flasks reached a peak density of 12.3 million cells/ml on the fourth day. Observations during the fieldwork indicated that the highest peak of plankton growth occurred on the fourth day, reaching a density of 13 million cells/ml. Between the second and sixth days, there was a continuous increase in growth, peaking at 1.8 million cells/ml on the sixth day. The advanced culture techniques for Thalassiosira sp. as natural feed for vannamei shrimp larvae (Litopenaeus vannamei) at BPIU2K, Karangasem, Bali, has demonstrated effective methods for optimizing plankton growth and quality.